2022
DOI: 10.1021/acs.est.1c03776
|View full text |Cite
|
Sign up to set email alerts
|

Acute Toxicity of Eight Aqueous Film-Forming Foams to 14 Aquatic Species

Abstract: Researchers have developed numerous per- and polyfluoroalkyl substances (PFAS)-free aqueous film-forming foam (AFFF) formulations to replace PFAS-containing AFFF used for fire suppression. As part of the Department of Defense’s Strategic Environmental Research and Development Program (SERDP), we examined the direct lethal effects of seven PFAS-free AFFF and a PFAS-containing AFFF on 14 aquatic species using a series of lethal concentration (LC50) tests. We assessed the LC10, LC50, and LC90 values using log–log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…PFAS are of a significant environmental concern since they are highly persistent, can bioaccumulate in organisms, and transport through maternal transfer. In work by Sunderland et al, the human exposure to PFAS and its epidemiologic evidence for impact on cancer, immune function, metabolic outcomes, and neurodevelopment are reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…PFAS are of a significant environmental concern since they are highly persistent, can bioaccumulate in organisms, and transport through maternal transfer. In work by Sunderland et al, the human exposure to PFAS and its epidemiologic evidence for impact on cancer, immune function, metabolic outcomes, and neurodevelopment are reviewed.…”
Section: Resultsmentioning
confidence: 99%
“…■ ENVIRONMENTAL IMPACTS OF F3: CURRENT RESEARCH Research into the environmental impacts of F3 is a relatively new field, with the first peer-reviewed papers on the topic published only in the past couple of years. At present, the available ecotoxicological data on foam formulations are limited to studies on acute toxicity in 14 freshwater and marine aquatic species, 55 acute toxicity in one terrestrial invertebrate (Caenorhabditis elegans), 56 acute oral toxicity in one avian species (northern bobwhite quail), 57 phytotoxicity in one plant species (Brassica rapa), 58 and aerobic biodegradation. 59 This limited body of research suggests that further investigation is needed to fully understand the environmental impacts of these foams, particularly when compared to the long-term effects of AFFF.…”
Section: Applicationsmentioning
confidence: 99%
“…In some cases, research has found that F3 can demonstrate equal or greater acute toxicity than C6 AFFF, particularly for aquatic species, which are often more sensitive than terrestrial species and mammals. 67 Some studies have also focused on the sublethal growth and reproductive impacts of these foams on worms 68 and plants. 45 However, it is important to distinguish between toxicity tests on a foam, formulation, or product and toxicological assessments based on individual components or constituents.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an up‐and‐down test procedure (OECD, 2008), Hossain et al (2022) observed northern bobwhite quail LD50s for all foams with ≥1500 mg formulated product/kg body weight. Further, these same foams have recently undergone an evaluation for acute toxicity in aquatic organisms; in 11 of 14 species, most of the fluorine‐free foams had greater acute toxicity than PFAS‐containing foam (Jones et al, 2022).…”
Section: Introductionmentioning
confidence: 99%